Argan oil trade and access to benefit sharing: A matter of economic survival for rural women of the Souss Massa, Morocco - Montanari, B. (2023)
Poverty eradication, environmental conservation, and the United Nations Sustainable Development Goals cannot be achieved without the input and participation of disadvantaged communities in developing mitigation strategies. Over the last few decades, the markets for natural resources as niche products have grown exponentially. Morocco’s production and international sales of argan oil are set to exceed current figures within the decade. We interviewed presidents of cooperatives in several villages in the Souss Massa region of Morocco to assess the current status of the argan oil trade, in particular women’s roles in production, their economic status, and whether they have access to benefit sharing (ABS). Our results reveal that control over the argan oil trade has shifted into intermediaries that supply larger corporations and that the survival of cooperatives and women’s access to vital income are increasingly threatened. We argue that the implementation of ABS is essential to preserve women’s access to income and their traditional knowledge associated with oil extraction processes and to ensure the conservation of argan ecosystems as prescribed by the Nagoya Protocol.